2014
DOI: 10.2478/bvip-2014-0069
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dietary Inulin Source on Piglet Performance, Immunoglobulin Concentration, and Plasma Lipid Profile

Abstract: The aim of the study was to evaluate the effect of an inulin source (aqueous or aqueous-alcoholic extract, dried chicory root, or dried Jerusalem artichoke tubers) on piglet performance, plasma lipid profile, and immunoglobulin concentration. The study was conducted on 534 piglets (44 litters) allocated to five nutritional groups: group I (control) -fed basal diet, groups II and III receiving basal diet supplemented with 2% of inulin (aqueous and aqueous-alcoholic extract respectively), and groups IV and V -4%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 20 publications
1
6
1
Order By: Relevance
“…Results showed that pigs born to FMTp sows (irrespective of postweaning treatment) were ϳ8.9 kg lighter at slaughter but were more feed efficient, given their lower RFI value. No improvements in weight gain or, indeed, FE were observed due to inulin inclusion in postweaning diets alone, which is contradictory to the findings of some previous studies (15) but in agreement with others (14,29). However, FE was improved when inulin was supplemented in the diet of weaner pigs born to FMTp sows, and although body weight was reduced, it may have a role in promoting the proliferation of beneficial bacterial populations implanted as a result of modulation of the maternal microbiota.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Results showed that pigs born to FMTp sows (irrespective of postweaning treatment) were ϳ8.9 kg lighter at slaughter but were more feed efficient, given their lower RFI value. No improvements in weight gain or, indeed, FE were observed due to inulin inclusion in postweaning diets alone, which is contradictory to the findings of some previous studies (15) but in agreement with others (14,29). However, FE was improved when inulin was supplemented in the diet of weaner pigs born to FMTp sows, and although body weight was reduced, it may have a role in promoting the proliferation of beneficial bacterial populations implanted as a result of modulation of the maternal microbiota.…”
Section: Discussioncontrasting
confidence: 99%
“…It has proven effective as a prebiotic in humans, but in pigs, results have been more contradictory (14). Nonetheless, a number of studies have found beneficial effects of inulin supplementation of pig diets, in terms of both improving growth performance and modulating the intestinal microbiota (15)(16)(17). In particular, supplementing weaner diets with inulin may be a useful way to counteract the susceptibility to infection and reduced growth rate associated with the stress of weaning, and a number of studies have demonstrated beneficial modulation of the intestinal microbiota and improved growth, gut health, and FE (16,18,19).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In studies on farm animals, the addition of prebiotics was found to stimulate the performance of animals, stabilize the microbiome of the digestive tract, and improve animal health status (10,13,15,24,54). On the other hand, other authors did not find such an impact (4,11).…”
Section: Tab 3 Effect Of the Dietary Level Of Two Types Of Inulin (mentioning
confidence: 99%
“…As FE is a major determinant of profitability in pig production, strategies to improve FE are continually being sought. To date, several approaches have been applied to increase beneficial gut bacterial populations with a view to improving FE, including probiotics ( 7 , 8 ), prebiotics ( 9 11 ), and synbiotics ( 12 , 13 ). Here, for the first time, we attempted to improve FE through fecal microbiota transplantation (FMT) to pregnant sows and/or their offspring.…”
Section: Introductionmentioning
confidence: 99%